Effects of restoration strategies on wetland: A case‐study of Xinqiang River National Wetland Park. (17th March 2022) - Lin, Yang; Wang, Deming; Farooq, Taimoor Hassan; Luo, Kai; Wang, Weiyue; Qin, Mingxun; Chen, Shiqi
Abstract: Accurately understanding the characteristics of a wetland ecological restoration plant communities and their species diversity relationships is the key to improving wetland management and biodiversity protection. To see the effects of restoration strategies implemented in Xinqiang River National Wetland Park, China, we studied 4 models for ecological restoration, namely protection and conservation (PC), reasonable utilization (RU), restoration and reconstruction (RR) and the building of constructed wetland (CW). We then analyzed the features of the plant communities, species diversity and soil properties, and carried out a correlation analysis between plant communities and the species diversity. Finally, we selected four key communities and analyzed their features and soil properties using a symmetric matrix. Results showed that the soil in the PC model had the highest amount of available phosphorus, available nitrogen and pH value. The soil had higher moisture content in the RU model and CW model than the other 2 models. Based on the correlation analysis, we found that there are obvious common characteristics among different ecological restoration types, that is, the diversity characteristics of tree layer, shrub layer and herb layer have obvious differentiation characteristics. We identified four features of the community characteristics that could improve species diversity: SA, TH, HH and SCD. The results of this study have provided a theoretical basis that there is a coupling relationship between ecological community characteristics and species diversity. The above coupling results have practical significance for maintaining good ecological structure and diversity protection.